2019
DOI: 10.1136/bmjspcare-2019-001809
|View full text |Cite
|
Sign up to set email alerts
|

Palliative cancer care: costs in a Brazilian quaternary hospital

Abstract: Palliative care (PC) improves the quality of life of patients with diseases such as cancer, and several studies have shown a reduction in costs among patients who use PC services when compared with those receiving standard oncological treatments. Most studies on PC costs are carried out in high-income countries. There is a lack of these types of studies in middle-income and low-income countries and of better evidence about this intervention.ObjectiveTo describe resource utilisation and costs among patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…Direct medical costs were categorised into seven cost items: consultation; diagnosis; treatment, including surgery, radiotherapy, chemotherapy, hormone therapy, combined modalities and palliative/supportive care; inpatient care; outpatient care; and follow-up care. In total, 11 studies presented data on mean direct medical costs [ 25 , 27 – 29 , 31 , 36 , 37 , 40 , 42 , 49 , 52 ]. Overall mean direct medical costs were $2740.18, which ranged from $1953.62 to $3526.74 per cancer patient.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct medical costs were categorised into seven cost items: consultation; diagnosis; treatment, including surgery, radiotherapy, chemotherapy, hormone therapy, combined modalities and palliative/supportive care; inpatient care; outpatient care; and follow-up care. In total, 11 studies presented data on mean direct medical costs [ 25 , 27 – 29 , 31 , 36 , 37 , 40 , 42 , 49 , 52 ]. Overall mean direct medical costs were $2740.18, which ranged from $1953.62 to $3526.74 per cancer patient.…”
Section: Resultsmentioning
confidence: 99%
“…Mean costs of palliative care were measured in four studies from Kenya [ 49 ], Vietnam [ 31 ], Brazil [ 42 ] and Turkey [ 27 ] with GDP per capita ranging from $1817 to $9042. The random-effects meta-analysis estimated direct medical costs attributed to palliative care as $3741.28 (95% CI, $2241.19, $5241.37).…”
Section: Resultsmentioning
confidence: 99%
“…In Europe, the cost of cancer care now accounts for up to 30% of total hospital expenditure and is growing (19). Consequently, there is an increasing need for countries to evaluate and re-evaluate the cost and value of treatments and services provided for patients with cancer including palliative care to improve allocative efficiency (20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of studies that have published on the costs of different aspects of cancer care in Brazil (20,21,23). This includes CT for people with mCRC in Brazil (24) and the cost effectiveness of different MABs for mCRC alongside CT (33,34).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies presented data on mean medical costs of combined surgery, chemotherapy and radiotherapy(23,39), with total mean costs of $9,888.14 [95% CI, $-4,480.83, $24,257.12] and a substantial heterogeneity (I 2 = 100%). One study reported that combined surgery and radiotherapy for any cancer type resulted in even higher associated mean medical costs ($1,749.35 [95% CI, $1,257.90, $2,240.80]; p < 0.00001)(39).Mean medical costs of palliative care were measured in four studies from Kenya (39), Vietnam(27), Brazil(41) and Turkey (23) with GDP per capita ranging from $1,817 to $9,042. The random-effects metaanalysis estimated the total mean medical costs attributed to palliative care as $3,741.28 [95% CI, $2,241.19, $5,241.37].…”
mentioning
confidence: 99%